A Sense of Brutality Philosophy after Narco-Culture (Amherst College Press, 2020)
Contemporary popular culture is riddled with references to Mexican drug cartels, narcos, and drug trafficking. In the United States, documentary filmmakers, journalists, academics, and politicians have taken note of the increasing threats to our security coming from a subculture that appears to feed on murder and brutality while being fed by a romanticism about power and capital. Carlos Alberto Sánchez uses Mexican narco-culture as a point of departure for thinking about the nature and limits of violence, culture, and personhood. A Sense of Brutality argues that violent cultural modalities, of which narco-culture is but one, call into question our understanding of "violence" as a concept. The reality of narco-violence suggests that "violence" itself is insufficient to capture it, that we need to redeploy and reconceptualize "brutality" as a concept that better captures this reality. Brutality is more than violence, other to cruelty, and distinct from horror and terror-all concepts that are normally used interchangeably with brutality, but which, as the analysis suggests, ought not to be. In narco-culture, the normalization of brutality into everyday life is a condition upon which the absolute erasure or derealization of people is made possible.